Peak power output, the lactate threshold, and time trial performance in cyclists - Bentley, D. J.; McNaughton, L. R.; Thompson, D.; Vleck, V. E.; Batterham, A. M. (Medicine & Science in Sports & Exercise, 2001)
Purpose: To determine the relationship between maximum workload (Wpeak), the workload at the onset of blood lactate accumulation (WOBLA), the lactate threshold (WLTlog) and the Dmax lactate threshold, and the average power output obtained during a 90-min (W90-min) and a 20-min (W20-min) time trial (TT) in a group of well-trained cyclists. Methods: Nine male cyclists (V2max 62.7 +/- 0.8 mL.kg-1.min-1) who were competing regularly in triathlon or cycle TT were recruited for the study. Each cyclist performed four tests on an SRM isokinetic cycle ergometer over a 2-wk period. The tests comprised 1) a continuous incremental ramp test for determination of maximal oxygen uptake (V2max) (L.min-1 and mL.kg-1.min-1); 2) a continuous incremental lactate test to measure Wpeak, WOBLA, WLTlog, and the Dmax lactate threshold; and 3) a 20-min TT and 4) a 90-min TT, both to determine the average power output (in watts). Results: The average power output during the 90-min TT (W90-min) was significantly (P < 0.01) correlated with Wpeak (r = 0.91), WLTlog (r = 0.91), and the Dmax lactate threshold (r = 0.77, P < 0.05). In contrast, W20-min was significantly (P < 0.05) related to V2max (L.min-1) (r = 0.69) and WLTlog (r = 0.67). The Dmax lactate threshold was not significantly correlated to W20-min (r = 0.45). Furthermore, WOBLA was not correlated to W90-min (r = 0.54) or W20-min (r = 0.23). In addition, V2max (mL.kg-1.min-1) was not significantly related to W90-min (r = 0.11) or W20-min (r = 0.47). Conclusion: The results of this study demonstrate that in subelite cyclists the relationship between maximum power output and the power output at the lactate threshold, obtained during an incremental exercise test, may change depending on the length of the TT that is completed.